2021
DOI: 10.3389/fneur.2021.669296
|View full text |Cite
|
Sign up to set email alerts
|

Ketogenic Diet in the Treatment of Super-Refractory Status Epilepticus at a Pediatric Intensive Care Unit: A Single-Center Experience

Abstract: Background: To evaluate the use of the ketogenic diet (KD) for treatment of super-refractory status epilepticus (SRSE) at a pediatric intensive care unit (PICU).Design: A retrospective analysis of all pediatric patients treated for SRSE with the KD at our center was performed using patient data from our prospective longitudinal KD database.Setting: SRSE is defined as refractory SE that continues or recurs 24 h or more after initiation of anesthetic drugs. We describe the clinical and electroencephalographic (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Patients on KD require special attention throughout surgical practices as various medical intervention procedures involve exposure of carbohydrates into the blood circulation. The epilepsy should be managed by excluding drugs such as propofol, a carbohydrate-comprising remedy to counteract post-surgical seizure incidents [159,160]. A disturbing effect of KDs on micronutrient levels was found in a case of a refractory epilepsy female patient who developed scurvy due to an insufficient level of vitamin C while on a KD [161][162][163].…”
Section: Keto Diet Complicationsmentioning
confidence: 99%
“…Patients on KD require special attention throughout surgical practices as various medical intervention procedures involve exposure of carbohydrates into the blood circulation. The epilepsy should be managed by excluding drugs such as propofol, a carbohydrate-comprising remedy to counteract post-surgical seizure incidents [159,160]. A disturbing effect of KDs on micronutrient levels was found in a case of a refractory epilepsy female patient who developed scurvy due to an insufficient level of vitamin C while on a KD [161][162][163].…”
Section: Keto Diet Complicationsmentioning
confidence: 99%
“…But most of these studies are adult based. A few studies have reported the effectiveness of K D for management of SRSE in paediatric patients due to various etiologies specifically FIRES [ [13] , [14] ]. In a case report with literature review by Prasoppokakorn et al, medium chain triglyceride based K D was reported to be beneficial in young adult patients with SRSE and AI encephalitis [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies highlight that the need for a fasting KD initiation is not necessary for KD efficacy and it was proposed that fasting increases the risk of hypoglycaemia. 39,73,77,85,141,182 Studies also propose the use of KDs earlier on in the epileptic journey, 83,91,99,122,149,156,185,291,299 specifically in LGS, 233 TSC, 271 infants, 60,75,119,161,282,329 DS, 118,163 DOOSE, 144,209 CDKL5, 140 FIRES and SRSE, 36,160,169,256,280,283 and the metabolic conditions GLUT1DS 114,272,286 and PDHD. 247,296 Recommendations for treating new onset-refractory SE, including FIRES, includes the advice to escalate treatment from ASMs not only to immunotherapy, but also to KD, as soon as possible in the treatment course.…”
Section: What Populations Have Been Included In the Research?mentioning
confidence: 99%